INFOGRAFIS SEBAGAI MEDIA KEBIJAKAN PERUSAHAAN DALAM PENCEGAHAN PENYEBARAN COVID-19 DI LINGKUNGAN MEDIA GROUP NETWORK - Wibowo, Bayu Adji; Toni, Ahmad (KOMITMEN: Jurnal Ilmiah Manajemen, 2022)
This study aims to determine the extent to which the role of infographics as a media to convey the message of Media Group Network policy in inhibiting the spread of Covid-19. As well as exploring the types of infographic posters used, such as How-to Infographic, Explanatory Infographic, Comparison Infographic, to List Infographic. In this qualitative research approach, the method used is ethnography where the author participates in the research problem, the approach used is semiotics approach. This approach was chosen so that researchers are more-free to explore the symbols in the infographic poster produced by the Media Group Network secretarial entity. The Media Group Network strategy of using infographics as a medium to convey corporate policy messages turned out to be quite effective in conveying information within the coverage of the Media Group Network, but in the case of a pandemic, this strategy does not function as the main internal media in the Media Group Network, but as a supporting media and reminder because the pandemic is a global event that must have been anticipated by the highest state authorities nationally. in addition, this study also concluded that a proper and simple design system is needed in order to attract the public's desire to read and understand the message.